The effect of violation prevention program by developing social skill on 6 age (60-72 months old) children - Ayyıldız, Tülay; Cimete, Güler (Marmara Üniversitesi Sağlık Bilimleri Enstitüsü Dergisi, 2012)
This research is a quasi-experimental study which was developed for the purpose of determining the effect of child and parent program for preventing violation behaviors of children at the age of 6 (60-72 months old) by developing their social skills. The sample is comprised of 67 children and parents (36 experiments, 31 controls). As data collection tool, Social Skill Rating Scale’s Interpersonal Skills, Anger Behavior Control and Adaptation to Alterations Skill, Coping With Peer Pressure Skill, Self-Control Skill and Listening Skills lower dimensions, Monitoring Chart of Verbal and Behavioral Violence in Children, Parent Attitude Scale and Parent Interview Form was used. Education programs which, for experiment group children, comprised 30 activities including empathy, problem solving skills and anger management subjects, and which, for parents, comprised four sessions on subjects of features of child at the age of 6 (60-72 months old), parent-child communication, punishment and reward methods in children, violence behavior, their causes and prevention approaches in children were performed. Findings; while any significant difference was not determined between first measurement scores of Social Skill Rating Scale in experiment and control group children, significant differences were determined in favor of experiment group in the second measurement in all sub dimensions except for Self-Control, and in all sub dimensions in the third measurement. It was seen that, Social Skill Rating Scale sub dimension and total score averages of experiment and control group children showed significant increase over time and that this increase was more in experiment group. In terms of violence behavior, however, violence behavior in experiment group showed decrease with statistically significant level compared to control group children. As a conclusion, this program, which is for preventing violence behavior in children by developing social skills is applicable and effective.
Keywords: Nursing, social skill, violence behaviors, 6 age (60-72 months) old group children